Low-gradient Structural Valve Deterioration in a Patient of Cardiac Sarcoidosis - Koizumi, Shintaroh (J Cardiovasc Echogr, 2017)
We report a case of structural valve deterioration, which occurred 7 years after aortic valve replacement in a 78-year-old male with cardiac sarcoidosis. His echocardiography showed low transprosthetic valve gradient and depressed left ventricular function. A dobutamine stress echocardiography was performed to identify his pathophysiology, and it revealed that his depressed left ventricular function was not due to cardiac sarcoidosis but to structural valve deterioration. Reoperation for structural valve deterioration was performed, and his left ventricular function recovered.